Violin Teaching in the New Millennium: In Search of the Lost Instructions of Great Masters - an Examination of Similarities and Differences Between Schools of Playing and How These Have Evolved, or Remembering the Future of Violin Performance - MASIN, GWENDOLYN CAROLINA HELENA (Trinity College Dublin. School of Drama, Film & Music. MUSIC, 2012)
This thesis addresses a number of issues that have developed in the concepts and practices of violin pedagogy and performance since World War II. In particular it identifies the ways in which cultural transnationality has diminished the distinctiveness of various historic schools of violin playing and pedagogy, and has led to practices and concepts within teaching that threaten a historically and artistically informed view of what it means to learn the instrument. It compares current practice with those that prevailed between the middle of the 18th century and the decades immediately after World War II, and identifies a lack of published treatises by contemporary pedagogues. A discussion of the genealogy of teaching between distinguished pedagogues of today and those of the 18th century identifies important issues of technique and of artistic heritage that are endangered, plus concepts that are maintained by the best teachers and must be preserved. A vast amount of data regarding this genealogy has been gathered so as to provide a far-reaching family tree that is accompanied by an infogram. The second part of the thesis consists of an extended discussion of the various approaches taken by the author's teachers (including Shmuel Ashkenasi, Herman Krebbers, Igor Ozim, Ana Chumachenco and Zakhar Bron) to specific technical and artistic challenges. It concludes that one of the most potentially valuable counterweights to these tendencies would be the establishment of an Internet database that would be available to students and pedagogues alike. Both the methodology and the content of this thesis would be a valid starting point for such a database.
APPROVED
Keywords: Violin teaching; Violin performance; Violin pedagogy; Gwendolin Mason thesis; classical music teaching; classical music lessons; classical music method; Trinity classical music; Lyric FM; BBC classical music; BBC classic FM; Music theory; Music practice; Infographic; Family tree